Assessment of the trabecular structure of mandibular condyles in patients with temporomandibular disorders using fractal analysis - Arsan, Belde; Kose, Taha Emre; Cene, Erhan; Ozcan, Ilknur (ELSEVIER SCIENCE INC, 2017)
Objectives. The aim of this study was to evaluate changes in the trabecular structure of the mandibular condyle in patients with temporomandibular disorders (TMDs) using fractal analysis. Study Design. A total of 100 patients ages 18 to 73 years were clinically assessed using the Diagnostic Criteria for Temporomandibular Disorders. The control group was age-and sex-matched with the patient group. Panoramic radiographs were obtained using a Kodak 8000 digital device with 73 kVp and 5 mA fixed parameters. The degree of degeneration in the mandibular condyles was calculated. Regions of interest (84 X 84 pixels) were selected within the cortical boundary of the mandibular condyle, and the fractal dimension (FD) was calculated using ImageJ version 1.48. Results. Radiographic degenerative changes were more frequently present and more severe in the patient group (P < .001). The mean value of FD was 1.22 +/- 0.06 in the patient group and 1.25 +/- 0.06 in the control group (P = .001). A significant decrease in FD was observed (P = .001) in the left temporomandibular joints of the patient group, whereas a nonsignificant decrease in FD was observed in the right temporomandibular joints (P = .073) as degenerative changes increased. Conclusions. Lower FD values were associated with more severe degenerative changes in the patient group. The trabecular structure of condyles in patients with TMD exhibited decreased complexity when erosive and sclerotic changes were evident. As a result, fractal analysis enhanced the use of panoramic radiography in detecting degenerative changes in patients with TMD. (Oral Surg Oral Med Oral Pathol Oral Radiol 2017;123: 382-391)
Keywords: RESEARCH DIAGNOSTIC-CRITERIA; INTERNAL DERANGEMENT; BONE CHANGES; DIMENSION; JOINT; RADIOGRAPHS; OSTEOARTHROSIS; OSTEOPOROSIS; RELIABILITY; MORPHOLOGY; Dentistry, Oral Surgery & Medicine